The Existence of Local Wisdom Based MSMEs in Supporting the Creative Economy of Sidenreng Rappang Regency - Henni Zainal (Jurnal Administrasi Bisnis, 2026)
This study aims to analyze the existence of local wisdom-based Micro, Small, and Medium Enterprises (MSMEs) in supporting the development of the creative economy in Sidenreng Rappang Regency. Local wisdom-based MSMEs have an important role in maintaining regional cultural identity while also being a driver of community economic growth. However, the development of globalization and digitalization requires MSMEs to be able to adapt to remain existent and competitive amidst modern market competition. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, in-depth interviews, and documentation of MSMEs, local governments, and local communities. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The focus of the research includes the form of local wisdom applied in MSME products, business development strategies, and the contribution of MSMEs to the regional creative economy. The results show that local wisdom-based MSMEs in Sidenreng Rappang Regency are able to maintain their existence through product innovation, utilization of digital media, and strengthening local cultural identity in each product produced. The existence of MSMEs not only increases community income, but also creates jobs and strengthens the regional creative economy sector. However, MSMEs still face various challenges, such as limited access to digital marketing, business capital, and improving the quality of human resources. Therefore, government support, digitalization training, and collaboration between stakeholders are needed to sustainably enhance the competitiveness of MSMEs based on local wisdom.